Harmonizing Spirituality At Work: A Pluralistic Prespective Of Multi-Faith Auditors - Cahya Arina, Natrabilla; Qomariyah, Alfiyatul (Universitas Muhammadiyah Pontianak, 2026)
This study explores how multi-faith auditors harmonize workplace spirituality as a coping mechanism to manage stress and uphold professional integrity. Prior research predominantly frames workplace spirituality within individual or single-faith perspectives, offering limited insight into interfaith harmonization in high-pressure professions. Employing an interpretative paradigm and Interpretative Phenomenological Analysis (IPA), this study draws on in-depth interviews with twelve auditors representing five major religions in Indonesia. The findings reveal spirituality as a pluralistic framework that strengthens ethical responsibility, psychological resilience, and social cohesion, underscoring the importance of spiritually inclusive work environments Keywords: Brand Awareness; Brand Trust; Electronic Word Of Mouth; Purchase Decision; Tokopedia; Consumer Behavior.